The Genetic Contribution to Drug Response in Spondyloarthritis: A Systematic Literature Review - Ortolan, Augusta; Cozzi, Giacomo; Lorenzin, Mariagrazia; Galozzi, Paola; Doria, Andrea; Ramonda, Roberta (Frontiers in Genetics, 2021)
Objective: Spondyloarthritis (SpA) are a group of diseases with a high heritability, whose pathogenesis is strongly determined by an interplay between genetic and environmental factor. Therefore, the aim of our study was to determine whether genetic variants could also influence response to therapy in SpA. Methods: A systematic literature review (SLR) was conducted in PubMed and Web of Science core collection, without publication-year restrictions (Last search 8th April 2021). The search strategy was formulated according to the PEO format (Population, Exposure, Outcome) for observational studies. The population was adult (≥ 18 years) patients with SpA. The exposure was inheritable genetic variations of any gene involved in the disease pathogenesis/drug metabolism. The outcome was response to the drug, both as dichotomous (response yes/no) and as continuous outcomes. Exclusion criteria were: 1) languages other than English. 2) case series, case reports, editorials and reviews 3) studies reporting genetic contribution to drug response only limited to extra-musculoskeletal features of SpA 4) epigenetic modifications. Quality of the included study was independently assessed by two authors. Results: After deduplication, 393 references were screened by 2 authors, which led to the final inclusion of 26 articles, pertinent with the research question, that were considered for qualitative synthesis. Among these, 10 cohort, 1 cross-sectional and 5 case-control studies were considered of at least good quality according to NOS. In studies about TNF-blockers therapy: 1) polymorphisms of the TNF receptor superfamily 1A/1B (TNFRSF1A/1B) genes were most frequently able to predict response 2)-238 and -308 polymorphisms of TNFα gene were studied with conflicting results 3) TNFα polymorphism rs1799724, rs1799964, -857, -1013, +489 predicted drug response in non-adjusted analysis 4) PDE3A rs3794271 had a linear relationship with DAS28 reduction after anti-TNFα therapy. DHFR polymorphism +35289 was able to predict response to methotrexate. Conclusions: our SLR highlighted the existence of a genetic component in determining drug response. However, further studies are warranted to better define quantify it.